Intelligent wargaming approach to increase course of action effectiveness in military operations - Yuksek, Burak; Guner, Guney; Karali, Hasan; Candan, Batu; Inalhan, Gokhan (American Institute of Aeronautics and Astronautics (AIAA), 2023)
In this study, an intelligent wargaming approach is proposed to evaluate the effectiveness of a military operation plan in terms of operational success and survivability of the assets. The proposed application is developed based on classical military decision making and planning (MDMP) workflow for ease of implementation into the real-world applications. Contributions of this study are threefold; a) developing an intelligent wargaming approach to accelerate the course of action (COA) analysis step in the MDMP which leads creating more candidate COAs for a military operation, b) generating effective tactics against the opposite forces to increase operational success, and c) developing an efficient, visual wargame-based MDMP framework for future systems that require a small team of operators to supervise a network of automated agents. Several example engagement scenarios are performed to evaluate the system capabilities and results are given. Moreover, fleet composition issue for automated agents is investigated and the fleet composer algorithm with hyperparameter tuning architecture is proposed.